Exposure to old formaldehyde compounds of liquid air freshener products on lung, heart and brain cell histology of mice (Mus musculus) - Delima Engga Maretha; Asnilawati Asnilawati; Vina Prisunarti Putri; Senja Senja; Tri Ayu; Muhammad Mustapha Adam (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.